Comparison of the Casting Accuracy of Monopren in Two Different Implant Systems - Elham Soltanpanah Dorbidi (Journal of Global Pharma Technology, 2017)
Statement of the problem the correct fit of implant-supported frameworks is obtained through taking a precise master cast which is quite similar to the patient’s intraoral orientation. The accuracy of implant casts depends on several factors including the impression technique and material, tray, implant angulations and depth, impression coping, the geometry of implant torque, and cast expansion. Purpose: this study aimed to evaluate the accuracy of open-tray and closed-tray impressions in two implant systems. Materials and method: two master casts of edentulous mandible were made of transparent acrylic resin. Bio horizon (n=30) and dio of implants (n=30) were inserted in either cast at 0 and 20° angles. Open- and closed-tray impressions were taken by using monopren material, and were poured with type iv stone cast. The related abutments were installed on the prepared casts. Digitizer in association with the 3d scanning system of atos software created point cloud of the casts and master casts. Finally, a comprehensive report of the deviations in x, y, and z axes were presented. Results: both the impression technique and implant system affected the impression accuracy significantly (p=0). but, the effect of implant angulations was statistically insignificant (p=0.793). Moreover, the interaction of implant system and impression technique was significant (p=0). However, no significant interaction was noted between the implant angulations and system or between the implant angulations and impression technique (p=0.944).conclusion: the impression technique and implant system play the key roles in the implants impression accuracy.Keywords: Impression accuracy; Impression technique; Implant system; Implant angulation; Impression material.